Smartwatch-monitored physical activity and myopia in children: a 2-year prospective cohort study - Chen, Daixi; Wang, Jingjing; Chen, Jun; Lu, Meng; Du, Yuchen; Zhu, Ziyan; Sankaridurg, Padmaja; Zhu, Zhuoting; Zhang, Bo; Du, Linlin; Yang, Jinliuxing; He, Xiangui; et al. (BMC medicine, 2025)
Background While outdoor time's protective role against myopia is established, the relationship between physical activity (PA) and myopia development remains unclear. This study aimed to determine the impact of PA on myopia in children. Methods In this prospective, school-based cohort study conducted in Shanghai from 2016–2018, children aged 6–9 years from 24 primary schools wore smartwatches for 1 year to record activity intensity and environmental status (indoor/outdoor). Activity load was calculated as a weighted sum of time spent in light (1 ×), moderate (2 ×), and vigorous (3 ×) activities. Myopia shift was measured by 2-year changes in spherical equivalent (SE) and axial length (AL). Limited myopia progression was defined as myopic shift ≤ -0.50 D over 2 years. Results Among 4306 participants (mean age 7.3 ± 0.6 years; 47.1% girls), mean daily activity times indoors were 134.26 ± 31.99, 9.05 ± 3.34, and 2.63 ± 2.71 min for light, moderate, and vigorous activities respectively, with corresponding outdoor times of 59.10 ± 17.71, 12.64 ± 4.79, and 2.21 ± 1.11 min. Activity load showed protective associations in both environments, stronger outdoors (β = 0.18; 95% CI, 0.10–0.27; p < 0.001) than indoors (β = 0.06; 95% CI, 0.003–0.12; p = 0.037). Children in the highest quartile of indoor activity (≥ 3.02 weighted hours/day) showed 22% higher odds of limited myopia progression (adjusted OR = 1.22; 95% CI, 1.00–1.50; p for trend = 0.048), while those with outdoor activity ≥ 1.47 weighted hours/day demonstrated 34–77% higher odds (adjusted OR: Q3 = 1.34, 95% CI 1.01–1.80; Q4 = 1.77, 95% CI 1.32–2.36; p for trend < 0.001). Outdoor activity load was particularly protective in non-myopic children (β = 0.15; 95% CI, 0.07–0.23; p < 0.001) and those with daily outdoor time < 120 min (β = 0.22; 95% CI, 0.11–0.33; p < 0.001), while indoor activity load was protective in Grade 2 students (β = 0.11; 95% CI, 0.03–0.20; p = 0.009) and children with ≥ 120 min of outdoor time (β = 0.23; 95% CI, 0.07–0.39; p = 0.006). Conclusions Activity load, integrating both time and intensity of PA, shows significant protective associations with myopic shift in both indoor and outdoor environments. This protective effect exists independent of light exposure, suggesting that PA might offer additional benefits for myopia prevention beyond the known effects of outdoor time.